2020
DOI: 10.1155/2020/8265054
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Oxidative Degradation of N-Methylpyrrolidone (NMP) in Microelectronic Fabrication Processes by Using a Multiplatform Analytical Approach

Abstract: During the construction of recording head devices, corrosion of metal features and subsequent deposition of corrosion by-products have been observed. Previous studies have determined that the use of N-methylpyrrolidone (NMP) may be a contributing factor. In this study, we report the use of a novel multiplatform analytical approach comprising of pH, liquid chromatography/UV detection (LC/UV), inductively coupled plasma optical emission spectroscopy (ICP-OES), and LC/mass spectrometry (LC/MS) to demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…At the same time, having nonpolar carbons and a large planar nonpolar region can lead to hydrophobic interactions between NMP and nonpolar molecules to form a complex . This specific structure of NMP is the basis for its unique physicochemical properties, and the use of NMP as a solvent, co-solvent, and complexing agent in different applications such as the pharmaceutical and electronics industries. Several studies showed that NMP could be used as potentially powerful scavengers of oxidizing agents. Despite the various advantages of NMP, its application to create a suitable medium to synthesize metal nanoparticles has not been systematically considered. Jeon and co-workers used oxidized NMP as a solvent and a reducing agent to synthesize silver nanoparticles .…”
Section: Introdutionmentioning
confidence: 99%
“…At the same time, having nonpolar carbons and a large planar nonpolar region can lead to hydrophobic interactions between NMP and nonpolar molecules to form a complex . This specific structure of NMP is the basis for its unique physicochemical properties, and the use of NMP as a solvent, co-solvent, and complexing agent in different applications such as the pharmaceutical and electronics industries. Several studies showed that NMP could be used as potentially powerful scavengers of oxidizing agents. Despite the various advantages of NMP, its application to create a suitable medium to synthesize metal nanoparticles has not been systematically considered. Jeon and co-workers used oxidized NMP as a solvent and a reducing agent to synthesize silver nanoparticles .…”
Section: Introdutionmentioning
confidence: 99%